Histomorphological spectrum of salivary gland tumors: a study at tertiary care teaching hospital of North Gujarat - Dr. Keyur Kumar Gulabbhai Patel; Dr. Anand Palas; Dr. Amit J Asari; Dr. Jigar Bachubhai Baria (Tropical Journal of Pathology and Microbiology, 2018)
Background: Salivary gland tumors (SGTs) are rare neoplasm of head and neck region. The salivary gland tumours vary widely in histopathological appearance. Also, epidemiological data of these tumors in various parts of the world are different. And so the study of SGTs for their biology and clinical characteristics can be helpful for a better understanding.Objectives: The objective of this study was to study types and new entities, common site of distribution and histomorphological spectrum of salivary gland tumors (SGTs).Materials and Methods: It was a retrospective followed by prospective study. Pertinent clinical history like age, duration of the lesion, site of the lesion, significant family and personal history, history of associated diseases was recorded. Specimens consisted of incisional biopsies were examined microscopically by the expert pathologist. Details of specimens noted in Performa include dimensions, appearance of external and cut surface and presence of lymph nodes, their size and number.Observations: Total 70 cases of SGTs could be included in the study. Among them 56 (80%) were benign and 14 (20%) were malignant. Parotid is commonest salivary gland involved with 75.71% of all tumors, followed by submandibular with 21.42% and minor salivary glands with 1(1.4%) of salivary gland tumors. among benign tumors Pleomorphic adenoma is most common with 70% of all benign SGTs followed by Warthin tumors (7%). Among malignant tumors commonest is Mucoepidermoid carcinoma with 14.28% of all SGTs. Female preponderance was clearly found in malignan at SGTs.Conclusion: Parotid is most common site for the SGT. And pleomorphic adenoma and the Warthin tumors are the common benign tumors involve parotid gland the most. Among malignant tumors mucoepidermoid carcinoma are the commonest with female preponderance. While other carcinoma like adenoid cystic carcinoma and SCC are also common.